A longitudinal study of summertime occupant behaviour and thermal comfort in office buildings in northern China. (1st October 2018) - Sun, Cheng; Zhang, Ran; Sharples, Steve; Han, Yunsong; Zhang, Hongrui
Abstract: The adaptive behaviour and thermal responses of building occupants can be responsible for significant uncertainties when comparing monitored and modelled building energy performance. A better understanding of the interaction of occupants and their buildings is necessary for managing this uncertainty and reducing discrepancies between predicted and actual energy use (commonly known as 'the performance gap'). This paper presents the results from a longitudinal study during a summer season of ten mixed-mode offices located in Harbin, a city in northern China, which experiences severe winters and warm summers. The study collected data from on-line daily surveys, field measurements of the local environment, occupants' experiences and adaptive control behaviours. Occupant-building interactions were analysed through observing adaptive behaviour, perceived thermal sensations in the physical environment, architectural geometric variables and personnel characteristics. The driving mechanisms for behaviours and feelings were also studied. The results showed a high probability of window opening for both day and night, and a high frequency of the use of a mix of cooling options, including fans and air conditioning, accompanied by natural ventilation in the summer season. The active interaction of the offices' internal environments with the outdoor environment motivated more connections of occupant thermal feelings with the outdoor physical variables. Relative humidity levels were potential key predictors for window opening, and the geometric parameters of offices, occupants' fan use and perceived thermal feelings also showed a level of predictive ability. Evaluating the nature of occupant feelings and behaviours interactions may inform and improve results from building performance-based design. Highlights: The window opening probability of occupants in north Chinese offices were investigated and analysed using surveys and physical monitoring to reveal patterns of occupant behaviour. During the hot summer season, relative humidity was found to be the more significant driver of window opening behaviour, instead of the indoor and outdoor temperature. Affected by the high rate of window opening, the perceived thermal feelings of occupants yielded a close connection with the outdoor climate variables for all types of mixed-mode offices. In northern China, the summer window opening behaviour closely interacted with architectural geometric parameters, other adaptive behaviours and occupants' thermal comfort.